Molecular Diversity between Salivary Proteins from New World and Old World Sand Flies with Emphasis on Bichromomyia olmeca, the Sand Fly Vector of Leishmania mexicana in Mesoamerica. - Maha Abdeladhim; Iliano V Coutinho-Abreu; Shannon Townsend; Silvia Pasos-Pinto; Laura Sanchez; Manoochehr Rasouli; Anderson B Guimaraes-Costa; Hamide Aslan; Ivo M B Francischetti; Fabiano Oliveira; Ingeborg Becker; Shaden Kamhawi; et al. (Public Library of Science (PLoS), 2016)
BACKGROUND:Sand fly saliva has been shown to have proteins with potent biological activities, salivary proteins that can be used as biomarkers of vector exposure, and salivary proteins that are candidate vaccines against different forms of leishmaniasis. Sand fly salivary gland transcriptomic approach has contributed significantly to the identification and characterization of many of these salivary proteins from important Leishmania vectors; however, sand fly vectors in some regions of the world are still neglected, as Bichromomyia olmeca (formerly known as Lutzomyia olmeca olmeca), a proven vector of Leishmania mexicana in Mexico and Central America. Despite the importance of this vector in transmitting Leishmania parasite in Mesoamerica there is no information on the repertoire of B. olmeca salivary proteins and their relationship to salivary proteins from other sand fly species. METHODS AND FINDINGS:A cDNA library of the salivary glands of wild-caught B. olmeca was constructed, sequenced, and analyzed. We identified transcripts encoding for novel salivary proteins from this sand fly species and performed a comparative analysis between B. olmeca salivary proteins and those from other sand fly species. With this new information we present an updated catalog of the salivary proteins specific to New World sand flies and salivary proteins common to all sand fly species. We also report in this work the anti-Factor Xa activity of Lofaxin, a salivary anticoagulant protein present in this sand fly species. CONCLUSIONS:This study provides information on the first transcriptome of a sand fly from Mesoamerica and adds information to the limited repertoire of salivary transcriptomes from the Americas. This comparative analysis also shows a fast degree of evolution in salivary proteins from New World sand flies as compared with Old World sand flies.